Analysis of Muscle Fibers of Blue Al-Junaidiyah Students - Iin Pratiwi; Muhammad Arkanul Arba" (International Journal of Experimental Sports Science Research, 2026)
Background: Muscle fiber type composition is a fundamental determinant of athletic performance and physical capacity. Identifying the predominant muscle fiber type in religious boarding school (pesantren) students provides valuable insights into their physical training needs. Objectives: This study aims to analyze the muscle fiber composition of 50 male students at Santri Al-Junaidiyah Biru Pesantren using the vertical jump test method as an indirect assessment tool. Methods: A descriptive quantitative approach was employed with a total sampling technique involving 50 male students aged 15–18 years. Muscle fiber type was assessed using the Bosco vertical jump protocol which differentiates Type I (slow-twitch) and Type II (fast-twitch) fibers based on jump performance indices. Results: The results showed that 56% of students (n=28) were classified as predominantly Type I (slow-twitch) muscle fiber, while 30% (n=15) were classified as Type II (fast-twitch), and 14% (n=7) showed mixed fiber composition. The mean jump index was 48.6 ± 6.2 cm. Conclusions: The majority of Santri Al-Junaidiyah Biru students have slow-twitch dominant muscle fibers, suggesting an inclination toward endurance-type activities. These findings have significant implications for designing physical education programs tailored to the students' physiological profiles.